PENGARUH WORD OF MOUTH, PRICE DISCOUNT DAN CITRA RASA TERHADAP LOYALITAS KONSUMEN MANDA CATERING SITUBONDO DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Veny Manda Crisyanti; Ediyanto Ediyanto; Randika Fandiyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Marketing is an activity, a series of institutions, and processes for creating, communicating, delivering, and exchanging offerings that have value for consumers, clients, partners, and society as a whole. This study aims to analyze and examine the effect of word of mouth, price discount, and taste on consumer loyalty at Manda Catering Situbondo, with consumer satisfaction as an intervening variable. The population in this study consists of Manda Catering consumers in Situbondo. The sample was selected using random sampling techniques. Data analysis and hypothesis testing were conducted using the Structural Equation Modeling – Partial Least Squares (PLS-SEM) approach. The results of the direct effect hypothesis testing using Smart PLS 3.0 indicate that word of mouth has a positive but insignificant effect on consumer satisfaction, price discount also has a positive but insignificant effect on consumer satisfaction, and taste has a significant positive effect on consumer satisfaction. Furthermore, word of mouth and price discounts have a positive but not statistically significant effect on consumer loyalty, while taste has a statistically significant positive effect on consumer loyalty. Consumer satisfaction is found to have a significant positive effect on consumer loyalty.